Analisis Pandangan Siswa Kelas VI SD Negeri Purbo 03 terhadap Pembelajaran Daring Via Zoom Meeting - Ariyanti Ariyanti; Ervina Eka Subekti; Ikha Listyarini (Universitas PGRI Semarang, 2021)
Internet-based learning that is carried out online has become very intense by teachers in Indonesia since the covid-19 pandemic, one of which is SD N Purbo 03. SD N Purbo 03 teachers as users of distance learning services have a very significant role in transferring knowledge, facilitate, and assist students in learning. So, before seeing further how the learning process through applications, it is very necessary to know in advance how the students view the current conditions and in particular the use of Zoom Meeting media as a media for distance learning. This study uses a qualitative method by presenting sources as research subjects. The results showed that online learning in class VI SD N Purbo 03 with Zoom Meeting was divided into three stages, namely the learning planning stage, learning implementation and evaluation. Students' views on online learning through Zoom Meetings based on student experiences show that Zoom Meeting gives a pleasant impression of learning because in the implementation of learning Zoom Meeting gives the impression of learning like in a school where students and teachers are connected to each other even though virtually, the successful implementation of Zoom Meeting as a learning medium can not be separated from the involvement of parents in monitoring the online learning process.